A Thirteen-Year-Old Girl with Cornelia de Lange Syndrome – The First Case Described in Litigation - Lalić, Hrvoje (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this paper is to accentuate importance of the expert witness role, occupational medicine specialist, in litigation. The OM specialist proved his importance in broad spectrum of administrative court proceedings, assessment of working capacity, and different type of claims. CASE REPORT: Here is presented a case of a 13-year-old girl suffering Cornelia de Langue syndrome. The occupational medicine specialist concludes that the girl’s claim toward the Ministry of Demography, Family and Social Affairs is legitimate. Expert witness representing the above ministry came to conclusion that the patient is not heavily disabled due to her mobility and regular school attendance. Due to hearing aid her hearing is satisfactory and she is capable of dressing and feeding herself. In 2012, the girl was diagnosed with Langer-Giedion syndrome 8q23.3-q24.13 deletions and due to the development of molecular diagnosis only in 2015 RAD 21 gene deletion was discovered and she was correctly diagnosed. On examination, occupational medicine specialist found the patient suffering heavy deformations of locomotor system, small hands and feet, genua valga, and flat feet. The hearing is severely impaired in right and moderately in her left ear. Her mother states that she stopped soiling bed at the age of 8 and at present when going to toilette during night she becomes disoriented, sleeps badly, and screams. In the morning, she is not capable of preparing her own food. The patient needs to be examined by endocrinologist, her body is covered in exostoses and she heavily depends on other people. CONCLUSION: The patient is heavily disabled and in need of help for essential functioning at least until completion of secondary education.